DEVELOPMENT OF THE MELODICA ENSEMBLE LEARNING MODEL FOR STUDENTS OF SANG TIMUR CATHOLIC ELEMENTARY SCHOOL IN SEMARANG - Christanto Hadijaya; Ricky Nelson; Trianus Homklom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study develops and evaluates a structured Melodica ensemble learning model for elementary school students in response to the limited availability of systematic and developmentally appropriate ensemble-based instruction in primary music education. Using a design-based research approach, the study included needs analysis, model design, expert validation, limited trials, and implementation evaluation with Grade 3–6 students at SDK Sang Timur Semarang. The model integrates five progressive stages (listening, imitating, reading symbols, performing with accompaniment, and reflection), supported by graded repertoire, ensemble arrangements, digital media, and color management as visual scaffolding. Functional harmonic accompaniment (I–IV–V) in C and G major was applied to reinforce tonal understanding. Results show an 85% improvement in notation reading, approximately 50% increased fingering accuracy in early stages, and significant gains in rhythmic precision, pitch accuracy, ensemble coordination, and learning motivation. The gradual removal of color support confirms its role as effective transitional scaffolding without dependency. This study offers a validated and implementable pedagogical framework for strengthening basic music literacy through ensemble-based learning in elementary education.